2016
DOI: 10.1158/1078-0432.ccr-15-2218
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Dose-Escalation Study of Linsitinib (OSI-906) and Erlotinib in Patients with Advanced Solid Tumors

Abstract: Purpose Cross-talk between type I IGF receptor (IGF1R), insulin receptor (INSR), and epidermal growth factor receptor (EGFR) mediates resistance to individual receptor blockade. This study aimed to determine the MTD, safety, pharmacokinetics, pharmacodynamics, and preliminary antitumor activity of linsitinib, a potent oral IGF1R/INSR inhibitor, with EGFR inhibitor erlotinib. Experimental Design This open-label, dose-escalation study investigated linsitinib schedules S1: once daily intermittent (days 1–3 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 49 publications
(77 reference statements)
2
47
0
Order By: Relevance
“…NCT00739453 A phase 1 dose-escalation study of OSI-906 and erlotinib (Tarceva) (Macaulay et al 2016) 1 Dec-2011 Advanced solid tumors Drug doses: linsitinib schedules (S): S1 = 50-600 mg/QD; S2 = 50-400 mg/ QD; S3 = 100/150 mg/BID in conjunction with 100-150 mg/QD erlotinib. Linsitinib/erlotinib combination was well tolerated.…”
Section: #17mentioning
confidence: 99%
See 1 more Smart Citation
“…NCT00739453 A phase 1 dose-escalation study of OSI-906 and erlotinib (Tarceva) (Macaulay et al 2016) 1 Dec-2011 Advanced solid tumors Drug doses: linsitinib schedules (S): S1 = 50-600 mg/QD; S2 = 50-400 mg/ QD; S3 = 100/150 mg/BID in conjunction with 100-150 mg/QD erlotinib. Linsitinib/erlotinib combination was well tolerated.…”
Section: #17mentioning
confidence: 99%
“…A phase 1 clinical trial completed in 2011 reports that co-treatment with OSI-906 and erlotinib is tolerable leading to effective IGF-1R/InsR phosphorylation reduction in advanced solid cancers such as non-small-cell lung cancer, pancreatic, colorectal and prostate (Tables 1 and 2; Ref #17, NCT00739453) (Macaulay et al 2016). Based on the indirect effects of metformin on IGF1R/ EGFR activity (Rozengurt et al 2010, Liu et al 2011, there may be value in testing novel metformin combination therapies.…”
Section: Igf1r and Egfrmentioning
confidence: 99%
“…43,44 This suggests no significant effect of linsitinib on erlotinib PK, consistent with findings in the phase I combination trial. 38 …”
Section: Resultsmentioning
confidence: 99%
“…2628 Previously, phase I results in a 91-patient advanced solid tumor study showed acceptable tolerability for combined linsitinib plus erlotinib, with no evidence of significant drug-drug interaction, as well as initial evidence of efficacy in patients with advanced solid tumors. 38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation